Violated contracts, inadequate career support, but still forgiveness: Key organizational factors that determine championing behaviors - De Clercq, D.; Pereira, R. (European Management Review, 2024)
To establish how and when psychological contract violations steer employees away from championing behaviors, this study addresses the mediating role of beliefs about inadequate career support and the moderating role of forgiveness climates, as perceived by employees. Survey data from 208 employees of a retail organization, along with a simultaneous estimation of mediation and moderation effects (Process macro), reveal that a sense of organizational betrayal undermines efforts to mobilize support for innovative ideas, because employees critique employers for offering limited career support. Perceptions of an organizational climate that forgives mistakes mitigate this harmful process. For championing research, this study unpacks an unexplored link between psychological contract violations and championing efforts, influenced by career-related adversity and organizational forgiveness. For practitioners, it pinpoints the danger that employees who feel betrayed might inadvertently make things more difficult, because they react with work-related complacency. Organizations should create benevolent internal environments to diminish this danger.